2019
DOI: 10.1101/570036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

7q11.23 Syndromes Reveal BAZ1B as a Master Regulator of the Modern Human Face and Validate the Self-Domestication Hypothesis

Abstract: Symmetrical 7q11.23 dosage alterations cause craniofacial and cognitive/behavioral phenotypes that provide a privileged entry point into the evolution of the modern human face and (pro-) sociality. We undertook a functional dissection of chromatin remodeler BAZ1B in neural crest stem cells (NCSCs) from a uniquely informative cohort of typical and atypical patients harboring 5 7q11.23 Copy Number Variants (CNVs). Our results reveal a key contribution of BAZ1B to NCSC in vitro induction and migration, coupled wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…There are certainly differences in human morphology as well as in genes when Neanderthals, Denisovans and anatomically modern humans are compared , and some changes are in genes affecting pathways in which neural crest cells are involved and that lead to changes in the cranium. In a recent study, Zanlella et al (2019) showed that there were changes in the chromatin remodeler BAZ1B in neural crest stem cells during the evolution of anatomically modern humans. They found that large-effect mutations in the regulatory region of this gene lead to DS-like cranial and neural disease-related variation in modern humans.…”
Section: Variation In Dna and In Gene Expressionmentioning
confidence: 99%
“…There are certainly differences in human morphology as well as in genes when Neanderthals, Denisovans and anatomically modern humans are compared , and some changes are in genes affecting pathways in which neural crest cells are involved and that lead to changes in the cranium. In a recent study, Zanlella et al (2019) showed that there were changes in the chromatin remodeler BAZ1B in neural crest stem cells during the evolution of anatomically modern humans. They found that large-effect mutations in the regulatory region of this gene lead to DS-like cranial and neural disease-related variation in modern humans.…”
Section: Variation In Dna and In Gene Expressionmentioning
confidence: 99%
“…A crucial relevant development has been the discovery that the chromatin remodeler BAZ1B in neural stem cells controls the evolution of the modern human face [76]. Contrary to [28] and other alternatives proposed, neural stem cells are deeply involved in domestication [13].…”
Section: Testing the Domestication Hypothesismentioning
confidence: 99%